2017
DOI: 10.35799/jm.6.2.2017.17817
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Model ARIMA-GARCH Untuk Memprediksi Harga Saham Bank BRI

Abstract: Model time series yang dapat mengakomodasi sifat heteroskedastik adalah model ARCH atau GARCH. Penelitian ini bertujuan untuk menerapkan model ARIMA-GARCH dalam memprediksi harga saham bank BRI. Hasil penelitian menunjukkan bahwa pada harga saham bank BRI terdapat unsur heteroskedastik. Model terbaik yang didapat pada harga saham bank BRI yaitu ARIMA(2,1,1)-GARCH(2,2). Model tersebut memiliki nilai koefisien determinasi atau  (R-squared) yaitu sebesar 0.99916 atau 99,91%Time series model which can accommodate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
0
0
1
Order By: Relevance
“…Untuk penelitian model ARIMA-GARCH pada Bank BRI, juga sudah pernah diteliti oleh [16]. Penerapan model ARIMA-GARCH tersebut digunakan untuk memprediksi harga saham pada Bank BRI.…”
Section: Pendahuluanunclassified
“…Untuk penelitian model ARIMA-GARCH pada Bank BRI, juga sudah pernah diteliti oleh [16]. Penerapan model ARIMA-GARCH tersebut digunakan untuk memprediksi harga saham pada Bank BRI.…”
Section: Pendahuluanunclassified
“…It also has as residual with lagged conditional volatility, and as ARCH component, and and as GARCH component. After the ARCH/GARCH model estimation, the ARCH Lagrange Multiplier (LM) test can be applied to the model to determine whether the data still have heteroscedasticity (Yolanda et al, 2017).…”
Section: Return= Logmentioning
confidence: 99%
“…Heteroscedasticity occurs when the residual variance in time series data is not constant, necessitating a combination of ARIMA and GARCH models. In the study by (Yolanda et al, 2017), the ARIMA (2,1,1)-GARCH(2,2) method was found to be effective in predicting the stock price of BRI, with an R-squared value of 0.99916 or 99.91%. In another study by (Ningsih, 2021), the GARCH (1,1) method was proven to be reliable, as the forecasted data closely approximated the actual data with a Mean Absolute Percentage Error (MAPE) value of 1.273% for the Daily Stock Price of PT BTPN Syariah.…”
Section: Introductionmentioning
confidence: 99%